GuidanceaAnd Counseling Services for Learning Difficulties for Samborejo Students (ABK) Pekalongan District - Sufia, Nila Vila; Muniroh, Siti Mumun; Qona’ah, Indah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
Every child has the right to receive a decent education in every school regardless of the child's abnormalities. From here a problem arises called learning difficulty. Special needs counseling services are special services and special practices rather than in general. The aim of this research is to determine the characteristics of ABK with specific learning difficulties and remedial services. The method used is descriptive qualitative, the technique is through observation and interviews. The results of the MI Samborejo School research showed that three children had learning difficulties. Service results The remedial service program is only for children with special needs, namely children who have difficulty reading, writing, and cannot understand questions. This service program is carried out after the children come home from school and only lasts for one hour. Learning to read starts from recognizing letters, reading two syllables to reading short sentences. Learning media uses reading books that contain pictures to encourage students with special needs to understand reading more easily because there are pictures. The remedial service program is carried out three times a week.